PENGGUNAAN MODEL PEMBELAJARAN REALISTIK MATERI BILANGAN BERPANGKAT (EKSPONEN) DI SMP NEGERI 5 TANIMBAR UTARA KABUPATEN KEPULAUAN TANIMBAR - yoseph batkunde; Priskila Embuai; Cartes Asbit Rangotwat (Mandalika Mathematics and Educations Journal, 2022)
The purpose of this study was to find out mathematics learning using a realistic learning model on exponent numbers in class IX of junior high school 5 north Tanimbar, Tanimbar Islands Regency. The subjects of this study were students of class IX of junior high school 5 north Tanimbar, Tanimbar Islands Regency, totaling 23 students. This research was carried out in 4 meetings, namely (1) the implementation of the initial test, (2) the implementation of the first learning, (3) the implementation of the second learning, (4) the implementation of the formative test. Quantitative data in the form of student learning outcomes obtained through tests. The results showed that : (1) there was an increase in student learning outcomes by learning using the PMR model.